Analysis of the Role of Investment in Economic Development Policy in the Tourism Sector in Deli Serdang Regency - Miftaloka, Ummu Hany; Imsar; Rahmani, Nur Ahmadi Bi (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the role of investment in economic development policies in the tourism sector in Deli Serdang Regency and its empowerment towards regional economic growth from an Islamic economic perspective. The research method used is a qualitative descriptive analytical approach utilizing secondary data from the Central Statistics Agency (BPS), the Tourism Office, and the Investment and One-Stop Integrated Services Office (DPMPTSP) of Deli Serdang Regency for the 2015–2024 period. The results show that tourism investment contributes positively to increasing Gross Regional Domestic Product (GRDP), creating jobs, and strengthening the creative economy of local communities. Programs such as the Kamu Market in Denai Lama Village and the development of Sibolangit nature tourism are examples of the successful synergy between investment policies and community economic empowerment. However, the effectiveness of the policy still faces obstacles in the aspects of inter-agency coordination, equitable distribution of investment between regions, and limited human resource capacity. From an Islamic economic perspective, tourism investment must be based on the principles of maslahah, 'adl (justice), and tawazun (balance) so that economic development does not only focus on material growth, but also ensures social welfare and environmental sustainability. The concept of khalifah fil ardh (vicegerent) emphasizes humanity's responsibility as stewards of the earth to ensure sustainable and ethical investments. Therefore, investment policy strategies in the tourism sector need to be directed at strengthening sustainable tourism investments based on Islamic values ​​to create inclusive, equitable, and environmentally just economic growth